2019
DOI: 10.3390/en12224283
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Price Forecasting Based on Multi-Resolution Singular Value Decomposition and Extreme Learning Machine Optimized by the Moth–Flame Optimization Algorithm Considering Energy and Economic Factors

Abstract: Carbon price forecasting is significant to both policy makers and market participants. However, since the complex characteristics of carbon prices are affected by many factors, it may be hard for a single prediction model to obtain high-precision results. As a consequence, a new hybrid model based on multi-resolution singular value decomposition (MRSVD) and the extreme learning machine (ELM) optimized by moth–flame optimization (MFO) is proposed for carbon price prediction. First, through the augmented Dickey–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Zhang et al decomposed the original data series by multi-resolution singular value decomposition method and forecasted the coal price by using MFO-optimized ELM model. Experimental results show the forecasting performance of the proposed model was superior to that of the contrast model (Zhang et al, 2019). However, the neural network model is a black box model which is difficult to interpret.…”
Section: Introductionmentioning
confidence: 93%
“…Zhang et al decomposed the original data series by multi-resolution singular value decomposition method and forecasted the coal price by using MFO-optimized ELM model. Experimental results show the forecasting performance of the proposed model was superior to that of the contrast model (Zhang et al, 2019). However, the neural network model is a black box model which is difficult to interpret.…”
Section: Introductionmentioning
confidence: 93%
“…Supply and demand components, such as number of distributed allowances or expected emissions, can usually be expected to define the CO 2 price, but the allowance market can also be affected by macroeconomic or financial market shocks [9]. Several authors [10][11][12][13][14][15] have analyzed the relationship between EUA prices and their fundamentals (prices of gas, coal, oil...) or the link between CO 2 prices and the stock market returns of the power sector (one of the most polluting industries). They concluded that, in the short run, EUAs evolve like financial assets due to the time delay in their response to changes in fuel prices or to a new technical situation.…”
Section: Forecasting Modelmentioning
confidence: 99%
“…It is generally accepted that economic variables behave like nonlinear processes [16]. Non-linearity is rather troublesome when modeling the dynamics of time series describing the evolution of such economic variables [12,14,15,17]. To overcome this issue, several methods have been proposed in the literature [10,17].…”
Section: Forecasting Modelmentioning
confidence: 99%
“…It is the world's first multinational emissions trading system, based on cap-and-trade, which provides a way to reduce emissions at the lowest economic cost. Carbon emissions can be effectively reduced by buying and selling carbon permits (Zhang et al, 2019). China is the world's second-largest emitter of greenhouse gases and is seen by many countries as the most promising market for reducing emissions, even though it is not constrained to do so.…”
Section: Introductionmentioning
confidence: 99%
“…(Sun and Huang, 2020) used variational mode decomposition (VMD) to decompose the first inherent mode function (IMF1), and improved the prediction effect through secondary decomposition. In (Zhang et al, 2019)' research, the carbon price is decomposed into approximate sequence and detailed sequence after the high-frequency components of previous carbon price data is eliminated by the multi-resolution singular value decomposition method, and the two-time series were used as the prediction input.…”
Section: Introductionmentioning
confidence: 99%